2019
DOI: 10.1051/0004-6361/201936244
|View full text |Cite
|
Sign up to set email alerts
|

Gaia DR2 white dwarfs in the Hercules stream

Abstract: Aims. We analyzed the velocity space of the thin and thick-disk Gaia white dwarf population within 100 pc looking for signatures of the Hercules stellar stream. We aimed to identify those objects belonging to the Hercules stream and, by taking advantage of white dwarf stars as reliable cosmochronometers, to derive a first age distribution. Methods. We applied a kernel density estimation to the UV velocity space of white dwarfs. For the region where a clear overdensity of stars was found, we created a 5-D space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…There are only seven isolated white dwarfs and two common proper motion pairs that are halo candidates, corresponding to less than 0.3% of the respective samples. While this result is just a factor of three smaller than the halo fraction identified by Torres et al (2019b) in their analysis of the 100 pc Gaia DR2 white dwarf sample, pre-Gaia results by Pauli et al (2006) and Richter et al (2007) found 2% and <5%, respectively, halo members in the SPY sample. A Gaia DR2 update on this sample leveled down the estimate to about 1% (Dimpel 2018).…”
Section: Kinematic and Dynamic Propertiesmentioning
confidence: 53%
See 1 more Smart Citation
“…There are only seven isolated white dwarfs and two common proper motion pairs that are halo candidates, corresponding to less than 0.3% of the respective samples. While this result is just a factor of three smaller than the halo fraction identified by Torres et al (2019b) in their analysis of the 100 pc Gaia DR2 white dwarf sample, pre-Gaia results by Pauli et al (2006) and Richter et al (2007) found 2% and <5%, respectively, halo members in the SPY sample. A Gaia DR2 update on this sample leveled down the estimate to about 1% (Dimpel 2018).…”
Section: Kinematic and Dynamic Propertiesmentioning
confidence: 53%
“…The random forest classification of the 100 pc sample presented by Torres et al (2019b) used Gaia DR2 astrometry and ages, but did not include radial velocities. Three of their halo candidates are isolated white dwarfs in our sample (numbers 0703, 1461, and 2014) and were also classified as halo members above.…”
Section: Kinematic and Dynamic Propertiesmentioning
confidence: 99%
“…For Hercules stream, it has three substructures. The age distribution is peaked at 4 Gyr and extend to very old age for Hercules a and Hercules b; and Hercules c has a more uniform age distribution from ∼ 2 − 10 Gyr (Torres et al 2019).…”
Section: Kinematic Ages Of Planet Host Stars In the Galactic Diskmentioning
confidence: 92%
“…Despite the biases that this assumption may induce, (e.g. Pauli et al 2006;Torres et al 2019a) some of the clustering properties of the sample can remain unaltered (Fuchs & Dettbarn 2011;Torres et al 2019b). In this sense, we use the integral of motion space as an appropriate tool for analyzing our sample (e.g Helmi et al 2006).…”
Section: Kinematics Of the Halo White Dwarf Samplementioning
confidence: 99%